JURNAL HUKUM ANALISIS YURIDIS PUTUSAN BEBAS DALAM TINDAK PIDANA KORUPSI - Laowo, Yonathan Sebastian (Institut Pendidikan Tapanuli Selatan, 2018)
Juridical analysis against the acquittal in corruption is a normative study in corruption of acquittal given by the judges.The method used is a normative juridical research is through library research is qualitative by using the rule of law so as to outline the problems which exist in accordance with the facts that occurred in the community so that it can be seen what the factors that influence the judge in giving acquittal against perpetrators of corruption. One of the problems that arise in the effort to eradicate corruption is with the acquittal of the perpetrators of corruption. If acquitted continues, it could encourage criminals or others who want to make corruption more daring. This situation will make it difficult for Indonesian nation clean of corruption, collusion and nepotism.     Results from this study showed that there are many external factors that make a judge gave the acquittal and the possibility to the public prosecutor to bring a legal action against the acquittal. This is confirmed by the formulation of the editorial article 244 Criminal Procedure Code, as follows: